Case Study dalam Mengatasi Anemia pada Remaja Putri di Keluarga dengan Model HEMA Coach (Health Education, Modifikasi prilAku, dan Coaching) - Teti Rahmawati (Faletehan Health Journal, 2018)
Adolescents are among the groups at risk of anemia caused by a lack of iron in the body with various precipitating factors. Interventions consisted of Health Education, Modification PrilAku, and CoacHing named HEMA Coach. The purpose of the intervention is the decreasing prevalence of anemia in the family. The research design is case study using family nursing approach to 10 families taken with purposive sampling technique. The results showed an increase in knowledge, attitude, and family skills in overcoming anemia problems in young women. Research recommendations are health promotion policy, monitoring on changes in the behavior of young women are carried out in a sustainable manner done continuously.